ANALISIS AKAD AS-SALAM DALAM JUAL BELI ONLINE DI TOKO CHAGIYA - Yahya, Roby Putra; Farid, Diana; Utama, Sofyan Mei; Zilliavirni, Ratu Tiara; Abdulah Pakarti, Muhammad Husni; Hendriana, Hendriana (LPPM STAI Muhammadiyah Probolinggo, 2023)
This research discusses the concept of the As-Salam contract in online buying and selling transactions at the Chagiya shop. The As-Salam contract is a form of contract in Islam that has an important role in maintaining the principles of justice and ethics in business. This research aims to analyze the application of the As-Salam contract in the context of online buying and selling at the Chagiya shop, as well as its impact on transaction actors and consumers. Qualitative method with descriptive analysis, this research uses a field approach (Field Research) by making direct observations of the activities carried out by the company. While the data collection techniques in this study used interviews with sellers and buyers at Chagiya Stores and library documentation (Library Research), after the data was collected, data analysis was carried out with several stages, namely data reduction, data presentation and drawing conclusions from what was obtained in this study. The conclusion obtained from this research is that buying and selling with the online system carried out by Toko Chagiya is included in the as-salam system using a written contract via the internet where the as-salam contract can be carried out by the two contract actors who are not in one assembly (place) then applied through pictures of products and types through the Instagram site. Both (contract actors) are brought together on one network site. The Online as-Salam System at Toko Chagiya is concluded that as-salam with an online system is permitted, because it fulfills the pillars and conditions of salam sale and purchase that have been determined by Shara' and fulfills the rules that apply in a transaction. This is reinforced by the opinions of Chagiya Shop buyers regarding the sale of their products, 95% say that the online service is satisfactory, the goods in the picture match the reality, and if there is a mistake from the store, the store is responsible. In addition, in practice, the author concludes that the contract carried out by Toko Chagiya is in accordance with the provisions of Fatwa DSN-MUI No.05/DSN-MUI/IV/2000. Where this online buying and selling does not contain elements that can damage it, such as usury, injustice, fraud and the like.